PISA READING LITERACY: ENCOUNTERING FEMALE AND MALE’ READING LITERACY ABILITY - Yuli Tiarina; Sri Wahyuni; Dewi Fitri; Niken Sakinah; Ahmad Fajar Afif (University of Kuningan, 2022)
Much research sounds that male students’ reading competency is lower than females’. This article, then, uncovers the cognitive processes of male and female students seen from the sample questions in the 2018 PISA. This descriptive research involved fifteen male and sixteen female students. They were tested to answer PISA sample test consisting 21 items. It was found that the students score in reading literacy is poor. The highest score was 76; the lowest score was 10; the average score was 31. The result proved that female students are better in reading literacy than males are. Among eight cognitive process, female students are good at accessing and retrieving information, integrating and generating inferences across multiple sources, assessing quality and credibility, reflecting on content and form, and detecting and handling conflict. While, male students are better in integrating and generating inferences. The implication of the research is the teachers should provide HOTS instructional methods.